2020
DOI: 10.26444/aaem/118898
|View full text |Cite
|
Sign up to set email alerts
|

Asbestosis hospitalizations in Poland (2006–2016): results from the National Hospital Discharge Registry

Abstract: Introduction and objective. Occupational asbestos exposure is one of the major public health issues. Although asbestos use in Poland has decreased, asbestosis continues to remain an important health concern in the area of occupational medicine. The aim of the study is to perform a descriptive analysis of hospitalization cases in patients suffering from asbestosis in Poland. Materials and method. The authors used hospital discharge records to conduct a retrospective, population-based study. To estimate the asbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In 2019, the global overall burden of NCDs due to occupational asbestos exposure was higher among males. Compared with females, males are more likely to engage in construction, railway, cement processing, and other industries with high asbestos exposure, with more frequent asbestos exposure [ 29 ]. The gender difference in mesothelioma cases is mainly related to occupational exposure and is more susceptible to the effect of asbestos exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the global overall burden of NCDs due to occupational asbestos exposure was higher among males. Compared with females, males are more likely to engage in construction, railway, cement processing, and other industries with high asbestos exposure, with more frequent asbestos exposure [ 29 ]. The gender difference in mesothelioma cases is mainly related to occupational exposure and is more susceptible to the effect of asbestos exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the effects of long-term contact with asbestos dust will be recorded for the next dozen or so years, which, according to the author of the study, should be a reason to consider implementing international criteria for diagnosing asbestosis in Poland [1]. In 2006-2016, hospitalizations caused by exposure to asbestos were recorded mainly in the southern regions of Poland, inter alia, in the Silesia voivodeship, which is caused by air pollution caused by asbestos emission from asbestos processing plants operating in these areas [2,3]. The World Health Organization has estimated that currently about 125 million people worldwide are exposed to harmful asbestos in the workplace, and about half of the deaths are due to cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006-2016, hospitalizations caused by exposure to asbestos were recorded mainly in the southern regions of Poland, inter alia, in the Silesia voivodeship, which is caused by air pollution caused by asbestos emission from asbestos emission asbestos processing plants operating in these areas [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…After the issuance of Commission Directive 1999/77/EC of 26 July 1999, the use of asbestos has been completely banned in more than 50 countries, while in others, such as the USA and New Zealand, its use has been greatly reduced ( 1 ). Nevertheless, there are still countries, especially developing ones, where this mineral is still used, and an increase in cases of asbestosis and other asbestos-related diseases (ARDs) has been recorded in recent years ( 2 ).…”
Section: Introductionmentioning
confidence: 99%